2016
DOI: 10.3847/1538-4365/227/2/22
|View full text |Cite
|
Sign up to set email alerts
|

On Variations of Pre-Supernova Model Properties

Abstract: We explore the variation in single star 15-30 M , non-rotating, solar metallicity, pre-supernova MESA models due to changes in the number of isotopes in a fully-coupled nuclear reaction network and adjustments in the mass resolution. Within this two-dimensional plane we quantitatively detail the range of core masses at various stages of evolution, mass locations of the main nuclear burning shells, electron fraction profiles, mass fraction profiles, burning lifetimes, stellar lifetimes, and compactness paramete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
171
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(175 citation statements)
references
References 181 publications
3
171
1
Order By: Relevance
“…These later evolutionary phases are a rich site of fascinating challenges that include the interplay between nuclear burning (Couch et al, 2015;Farmer et al, 2016;Jones et al, 2017;Müller et al, 2016), convection (Meakin and Arnett, 2007;Viallet et al, 2013), rotation (Chatzopoulos et al, 2016;Heger et al, 2000;Rogers, 2015), radiation transport (Jiang et al, 2015(Jiang et al, , 2016, instabilities (Garaud et al, 2015;Wheeler et al, 2015), mixing (Maeder and Meynet, 2012;Martins et al, 2016), waves (Aerts and Rogers, 2015;Fuller et al, 2015;Rogers et al, 2013), eruptions (Humphreys and Davidson, 1994;Kashi et al, 2016;, and binary partners (Justham et al, 2014;Marchant et al, 2016;Pavlovskii et al, 2017). This bonanza of physical puzzles is closely linked with compact object formation by corecollapse supernovae (e.g., Eldridge and Tout, 2004;Özel et al, 2010;Perego et al, 2015;Sukhbold et al, 2016;Suwa et al, 2015;Timmes et al, 1996) and the diversity of observed massive star transients (e.g., Ofek et al, 2014;Smith et al, 2016;Van Dyk et al, 2000).…”
Section: B Helium Burning In Massive Starsmentioning
confidence: 99%
See 1 more Smart Citation
“…These later evolutionary phases are a rich site of fascinating challenges that include the interplay between nuclear burning (Couch et al, 2015;Farmer et al, 2016;Jones et al, 2017;Müller et al, 2016), convection (Meakin and Arnett, 2007;Viallet et al, 2013), rotation (Chatzopoulos et al, 2016;Heger et al, 2000;Rogers, 2015), radiation transport (Jiang et al, 2015(Jiang et al, , 2016, instabilities (Garaud et al, 2015;Wheeler et al, 2015), mixing (Maeder and Meynet, 2012;Martins et al, 2016), waves (Aerts and Rogers, 2015;Fuller et al, 2015;Rogers et al, 2013), eruptions (Humphreys and Davidson, 1994;Kashi et al, 2016;, and binary partners (Justham et al, 2014;Marchant et al, 2016;Pavlovskii et al, 2017). This bonanza of physical puzzles is closely linked with compact object formation by corecollapse supernovae (e.g., Eldridge and Tout, 2004;Özel et al, 2010;Perego et al, 2015;Sukhbold et al, 2016;Suwa et al, 2015;Timmes et al, 1996) and the diversity of observed massive star transients (e.g., Ofek et al, 2014;Smith et al, 2016;Van Dyk et al, 2000).…”
Section: B Helium Burning In Massive Starsmentioning
confidence: 99%
“…The 15 and 25 M models were calculated from the pre-main sequence to extinction of core He burning, defined as the time when the central mass fraction of He has fallen below 1 × 10 −5 . Other than the specified 12 C(α,γ) 16 O reaction rate, models with the same initial mass assume identical input physics assumptions (e.g., Farmer et al, 2016;Jones et al, 2015). An overview of the model results using the 12 C(α, γ) 16 O reaction rate from this work is given in Table XX. Throughout this section a comparison to the rate from this work is made to that of Kunz et al (2002), as they are propagated through different stellar models.…”
Section: Astrophysics Implicationsmentioning
confidence: 99%
“…The MESA runs used here are the same as those in Farmer et al (2016), where technical details can be found. Each star is modeled as a single, non-rotating, non-mass losing, solar metallicity object.…”
Section: Neutrino Production and Stellar Evolutionmentioning
confidence: 99%
“…This final instant is defined as t = t c = 0, and all the earlier times t (t < 0) will be defined relative to it, so that −t > 0 will indicate the time-to-collapse. The progenitor models used here are single, non-rotating, non-mass losing stars with a solar metallicity (i.e., mass fraction Z = 0.02 of elements heavier than He) and a solar abundance distribution from Grevesse and Sauval (1998); see Farmer et al (2016) for more details. Note that the range of masses we consider covers some of the diversity expected in the final outcome of the collapse: while the progenitors with lower mass are likely to generate a strong shockwave, resulting in a robust supernova explosion, the heavier ones (M = 25, 30 M ⊙ ) were found to be candidates for direct black hole formation (without explosion, a "failed supernova"), due to their greater compactness (see, e.g.…”
Section: The Calculation: Technical Aspects Inputs and Outputsmentioning
confidence: 99%
“…We use the models from Farmer et al (2016) with ∆M max = 0.1, where ∆M max specifies the maximum cell mass, and MESA's δ mesh = 1.0, where δ mesh controls the relative variance between cells. The combination of these two settings results in ≈ 1000 − 2000 spatial zones at core collapse.…”
Section: The Calculation: Technical Aspects Inputs and Outputsmentioning
confidence: 99%